TEACHING WRITING USING THINK-PAIR-SHARE VIEWED FROM STUDENTS’ LEVEL OF RISK-TAKING - Ningtyas Orilina Argawati; Lilis Suryani (English Review: Journal of English Education, 2017)
Writing is considered as the most difficult skill to master compared with the other skills because it involves many language elements such as content, organization, vocabulary, grammar and mechanics. The research examines the effect of two independent variables (Think-Pair-Share and Direct instruction method) on dependent variable (Writing Descriptive skill). The samples were class A1 2016 as the experimental class and A3 2016 as the control class. Each class consisted of 32 students. The instruments used covered the risk-taking’s questionnaire and writing test. Before applying the questionnaire of risk-taking, it was tried out to class A2 2016 to find out the validity and the reliability of the instrument. Meanwhile, before conducting the writing test, it needs to test the readability of the writing instruction. The treatment was conducted in eight meetings, and the 9th meeting was allocated for the post-test. The data were then analyzed using ANOVA and Tukey test. From the analysis, it reveals that: (1) Think-Pair-Share is significantly different from direct instruction method to teach writing; (2) the students with high level of risk-taking have better writing than those with low level of risk-taking; and (3) there is an interaction between teaching methods and the students’ level of risk-taking. Even though Think-Pair-Share is effective to teach writing, teachers must consider about the students’ condition, in this case their level of risk-taking.Keywords: Think-Pair-Share, Direct instruction method, Writing descriptive text, Risk-Taking